2015
DOI: 10.1016/j.addbeh.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Randomized trial of a secondhand smoke exposure reduction intervention among hospital-based pregnant women

Abstract: These results should encourage health professionals to educate pregnant women regarding the harms of SHS while both empowering and equipping them with the tools to confront their family members and effectively reduce their SHS exposure while promoting smoke-free social norms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 21 publications
1
38
0
Order By: Relevance
“…It may be said that HL could be effective in reducing perceived barriers through increasing perceived severity and self-efficacy. This finding is consistent with the results of studies by Atabila and Eleanor (17) and Chi et al (19). This finding is remarkably in contrast to the study findings of Kazemi (18) in which perceived barriers did not have significant differences over time in the experimental group compared to the control group.…”
supporting
confidence: 92%
“…It may be said that HL could be effective in reducing perceived barriers through increasing perceived severity and self-efficacy. This finding is consistent with the results of studies by Atabila and Eleanor (17) and Chi et al (19). This finding is remarkably in contrast to the study findings of Kazemi (18) in which perceived barriers did not have significant differences over time in the experimental group compared to the control group.…”
supporting
confidence: 92%
“…The details of the development process and content of the teaching materials can be found elsewhere. [ 10 ]…”
Section: Methodsmentioning
confidence: 99%
“…One previous study from Taiwan using a randomized controlled design has demonstrated that educational interventions based on this expanded HBM successfully enhance the capability of pregnant women to avoid and refuse SHS. [ 10 ] In that study, the intervention group demonstrated higher levels of readiness to refuse SHS and was more motivated to engage in SHS preventative actions than the comparison group. Similar findings were reported by Kazemi et al in Iran.…”
Section: Introductionmentioning
confidence: 97%
“…Considering that in smaller cities men spend most of their time with their families, creating a smoke-free home requires a couple of hours of not smoking and perception of barriers of not smoking would be accompanied with ETS exposure of women. Some reports have mentioned that educational efforts based on HBM have not been successful in quitting cigarette permanently and completely [25]. So, this study revealed that although men have strong motivations for conducting behaviors to ensure the health of the baby during pregnancy [17], but perception of threats of ETS exposure could not also create a smoke-free home for wives.…”
Section: Discussionmentioning
confidence: 83%